Fragments Within Fragments: The Collective Negotiation of Exquisite Corpse Drawings - Ardianta, Defry Agatha; Yatmo, Yandi Andri; Atmodiwirjo, Paramita (Interiority, 2025)
This paper argues for the critical role of collective drawings as a form of representation that highlights the open process. The open process of collective drawing involves actions performed by multiple actors and actions that are not limited to producing drawings together but also require the expression of ideas. Collective drawing encourages negotiations among fragments of the drawing, which opens up various possibilities of representations within the interiority discourse. Exquisite corpse drawings made by Surrealist artists occupy an influential position as drawings produced via an open process regulated by the internal mechanism, manifesting as a continuous act of drawing. This study on exquisite corpse drawings is conducted by dissecting the drawing fragments and examining how the head–torso–feet relationship is negotiated within them. The study reveals that layers of negotiation among fragments represent how the collective act of drawing works. This finding contributes to expanding the internal logic and system of a collective drawing process, allowing diverse interpretations and articulation of the representation works.